2021
DOI: 10.1177/1176934321999640
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Malaria Parasites in Ghana Show Signatures of Balancing Selection at Artemisinin Resistance Predisposing Background Genes

Abstract: Sub-Saharan Africa is courting the risk of artemisinin resistance (ARTr) emerging in Plasmodium falciparum malaria parasites. Current molecular surveillance efforts for ARTr have been built on the utility of P. falciparum kelch13 ( pfk13) validated molecular markers. However, whether these molecular markers will serve the purpose of early detection of artemisinin-resistant parasites in Ghana is hinged on a pfk13 dependent evolution. Here, we tested the hypothesis that the background pfk13 genome may be present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The current study demonstrated that there is clonal expansion of P . falciparum infections in the Central region with 55.5% of the study participants having between 2–6, similar to the 56% prevalence reported by Tandoh et al [ 44 ]. Furthermore, the prevalence of polyclonal infection also corroborates with findings on parasite diversity in other parts of Ghana, which concluded that P .…”
Section: Discussionsupporting
confidence: 88%
“…The current study demonstrated that there is clonal expansion of P . falciparum infections in the Central region with 55.5% of the study participants having between 2–6, similar to the 56% prevalence reported by Tandoh et al [ 44 ]. Furthermore, the prevalence of polyclonal infection also corroborates with findings on parasite diversity in other parts of Ghana, which concluded that P .…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies showed population bottlenecks and/or balancing selection when positive Tajima’s D values were determined for a population [ 39 , 40 ]. The positive Tajima’s D values of all tea populations here suggest that they all underwent population bottlenecks and/or balancing selection (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that positive Tajima’s D values indicated population bottlenecks and/or balancing selection [ 39 , 40 ]. Positive Tajima’s D values were observed in all populations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that there exist population bottlenecks and/or balancing selection when the positive Tajima's D values was detected in a population [43,44]. The positive Tajima's D values were observed in all these populations, suggesting that these populations existed population bottlenecks, and/or balancing selection (Table 2).…”
Section: Genetic Diversity Of Cultivated-type Tea Plantsmentioning
confidence: 76%